2017
DOI: 10.1002/app.45858
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun PAN–GO composite nanofibers as water purification membranes

Abstract: Varying amounts of exfoliated graphene oxide (GO) are systematically incorporated into nanoscale polyacrylonitrile (PAN) fibers via an electrospinning method. Subsequent treatment of the PAN–GO composite nanofibers under a moderate temperature and high pressure leads to the formation of membrane sheets with enhanced mechanical properties. scanning electron microscope, Fourier transform infrared spectroscopy, and contact angle measurements confirm the successful incorporation of the GO into the PAN nanofiber me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(55 citation statements)
references
References 45 publications
1
54
0
Order By: Relevance
“…We have also evaluated the particulate filtration performance of the ZPC‐Ag membrane by using a simple custom made dead‐end filtration set up (Supporting Information Section 7, Figure S8). DI water containing polystyrene beads (size: 1.1 μm mean diameter) was made to pass through the membrane by applying a constant pressure of 0.8 bar and water flux is calculated . It is observed that the ZPC‐Ag membrane effectively filtered out the polystyrene beads which are seen accumulated on the surface of the nanofibers (Supporting Information Section 7, Figure S9).…”
Section: Resultsmentioning
confidence: 99%
“…We have also evaluated the particulate filtration performance of the ZPC‐Ag membrane by using a simple custom made dead‐end filtration set up (Supporting Information Section 7, Figure S8). DI water containing polystyrene beads (size: 1.1 μm mean diameter) was made to pass through the membrane by applying a constant pressure of 0.8 bar and water flux is calculated . It is observed that the ZPC‐Ag membrane effectively filtered out the polystyrene beads which are seen accumulated on the surface of the nanofibers (Supporting Information Section 7, Figure S9).…”
Section: Resultsmentioning
confidence: 99%
“…Without heat treatment, all the as-spun PAN fibrous membranes showed a superhydrophilic surface (insets in Figure 1b,c), which is similar to the literature reports. [44,45] For PAN-1060 and PAN-450, the water contact angle (WCA) was 4.3° ± 0.9° and 2.7° ± 0.4°, respectively. When the PAN fibrous membrane was subjected to the heat treatment, no obvious change was found in fiber morphology except for surface wettability.…”
Section: Wwwadvmatinterfacesdementioning
confidence: 99%
“…The BSA studies are also beneficial to assess the anti-fouling assets of the materials. The findings were associated with cellulose acetate and PAN conventional ENMs to prove efficacy in aqueous filtration [107]. GO-PAA hydrogel nanocomposites have also been formed utilizing cross-linking chemistry.…”
Section: Multicomponent Electrospun Polymer Nanofiber Membranesmentioning
confidence: 99%